PARASITOFAUNA OF TILAPIA CAUSE MORTALITIES IN FINGERLINGS IN TWO FISHFARMS, LIMA, PERU - Gonzales-Fernández, Julio G. (2012)
The parasitofauna in tilapia Oreochromis spp., causing mortality in fingerlings in two cultivation centers, Lima, Peru, was evaluated. We analyzed 50 specimens of 4.0 to 7.0 cm in total length of tilapia grown in greenhouse-like systems and ponds. The gills of each sample were tested and the preparations were observed microscopically. The presence of the monogenean Gyrodactylus sp. (70% of prevalence) and two ciliate protozoa, Trichodina sp. (70%) and Ambiphrya (syn. Scyphidia) sp. (83.3%) was recorded. Histological changes in infected gills were observed and some cases, the presence of many aneurysms. 20 mL was applied in 100 L of diluted formaldehyde for one h per day for one week to eliminate or minimize the parasitic mortality.